Penggunaan Media Online Dalam Praktek Sosial Pekerja Seks Komersial - Surya Iflah El Ardhi; wahyu pramono (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The COVID-19 pandemic affects various aspects of human life, including commercial sex workers. The existence of restrictions on community activities makes commercial sex workers unable to conduct transactions directly so they must use online media to attract customers. This study aims to describe the use of online media and explain the structures that hinder and support the social practice of prostitution. The research was carried out using qualitative methods with descriptive research type. Informants in this study were obtained using the snowballing technique. The data were obtained using in-depth interview techniques and involved observation. The research was conducted in the city of Padang. The results showed that michat and twitter are online media applications that are widely used by commercial sex workers in attracting customers. Meanwhile, there are three structures that hinder the social practice of online prostitution, namely: 1) Fear of raids 2) Religion 3) Norms. Meanwhile, there are four enabling structures for the social practice of online prostitution, namely: 1) Place safety 2) Understanding of norms 3) Understanding of law and 4) Social media